The path to growth resilience: A serial mediation model linking temporal coherence to goal clarity and cognitive curiosity - Juan He; Hao Jin (PLoS ONE, 2026)
Fostering growth resilience is critical for college students to succeed and develop amidst academic and social environment. Temporal coherence — a balanced integration of past, present, and future perspectives — is recognized as important, yet the mechanisms linking it to growth resilience remain unclear. This study aimed to examine the effect of temporal coherence on growth resilience among college students and to test the serial mediating roles of goal clarity and cognitive curiosity. The study adopted a cross-sectional research design and administered an anonymous questionnaire to 452 Chinese college students (50.4% male and 49.6% female) via an online survey platform. The measures included the Zimbardo Time Perspective Inventory (ZTPI), the Goal Clarity Scale (GCS), the Cognitive Curiosity Scale, and the Chinese version of the Connor-Davidson Resilience Scale (CD-RISC). Hypothesis testing was conducted using Structural Equation Modelling (SEM) and the bias-corrected bootstrap method. The results indicated significant positive correlations among temporal coherence, goal clarity, cognitive curiosity, and growth resilience (r = 0.56–0.71, p < 0.01).. Structural equation model demonstrated good fit (χ²/df = 2.41, CFI = 0.961, TLI = 0.954, RMSEA = 0.056). Temporal coherence directly influenced growth resilience (β = 0.22, p = 0.002) and also exerted indirect effects through three pathways: via goal clarity alone (effect = 0.12), via cognitive curiosity alone (effect = 0.10), and via the serial mediation of goal clarity then cognitive curiosity (effect = 0.15). The serial mediated path accounted for 25.4% of the total effect, which was the indirect path with the largest effect size. Therefore, temporal coherence is an important predictor of growth resilience, primarily mediated through the sequential mechanism of enhancing goal clarity, which in turn stimulates cognitive curiosity.. This study reveals an intrinsic pathway from coherent time perception to resilient growth and highlights that interventions targeting time perspective, goal setting, and curiosity stimulation can effectively promote resilience in educational practice.